Engineering Immune Cells for in vivo Secretion of Tumor-Specific T Cell-Redirecting Bispecific Antibodies - Blanco, Belén; Ramírez-Fernández, Ángel; Alvarez-Vallina, Luis (Frontiers in Immunology, 2020)
Immunotherapeutic approaches based on the redirection of T cell activity towards tumor cells are actively being investigated. The impressive clinical success of the continuously intravenously infused T cell-redirecting bispecific antibody (T-bsAb) blinatumomab (anti-CD19 x anti-CD3), and of engineered T cells expressing anti-CD19 chimeric antigen receptors (CAR-T cells) in hematological malignancies, has led to renewed interest in a novel cancer immunotherapy strategy that combines features of antibody- and cell-based therapies. This emerging approach is based on the endogenous secretion of T-bsAbs by engineered T cells (STAb-T cells). Adoptive transfer of genetically modified STAb-T cells has demonstrated potent anti-tumor activity in both solid tumor and hematologic preclinical xenograft models. We review here the potential benefits of the STAb-T strategy over similar approaches currently being used in clinic, and we discuss the potential combination of this promising strategy with the well-established CAR-T cell approach.